EPIPHANY OF RATNA INDRASWARI IBRAHIM AS AUTHOR - Susilo Mansurudin (Fakultas Sastra Universitas Negeri Malang, 2018)
Abstract: Epiphany is a crucial event encountered by an individual which gives him/her an insight in his/her journey of meaning making to life. This qualitative research aims at finding out epiphany of RII represented in her anthology of short stories, novelets, novels. The research has found out that RII, as a diffable figure, is mentally capable of creating extraordinary works which are: (a) useful for others, (b) inspiring, (c) affecting surrounding people to be stronger, and (d) mostly true-story based. As a writer, RII's epiphany covers three main issues, i.e. (i) humanity epiphany, (ii) femininity epiphany, and (iii) diffability epiphany. permalink/DOI: dx.doi.org/10.17977/um015v46i12018p044